Neurogenetic Impairments of Brain Reward Circuitry Links to Reward Deficiency Syndrome (RDS): Potential Nutrigenomic Induced Dopaminergic Activation - Blum, K (2012)
Work from our laboratory in both in-patient and outpatient facilities utilizing the Comprehensive Analysis of Reported Drugs (CARD)(™) found a significant lack of compliance to prescribed treatment medications and a lack of abstinence from drugs of abuse during active recovery. This unpublished, ongoing research provides an impetus to develop accurate genetic diagnosis and holistic approaches that will safely activate brain reward circuitry in the mesolimbic dopamine system. This editorial focuses on the neurogenetics of brain reward systems with particular reference to genes related to dopaminergic function. The terminology “Reward Deficiency Syndrome” (RDS), used to describe behaviors found to have an association with gene-based hypodopaminergic function, is a useful concept to help expand our understanding of Substance Use Disorder (SUD), process addictions, and other obsessive, compulsive and impulsive behaviors. This editorial covers the neurological basis of pleasure and the role of natural and unnatural reward in motivating and reinforcing behaviors. Additionally, it briefly describes the concept of natural dopamine D2 receptor agonist therapy coupled with genetic testing of a panel of reward genes, the Genetic Addiction Risk Score (GARS). It serves as a spring-board for this combination of novel approaches to the prevention and treatment of RDS that was developed from fundamental genomic research. We encourage further required studies.